Pengembangan Kemampuan Berpikir Kreatif Mahasiswa Melalui Pembelajaran Berbasis Proyek Pada Pembuatan Model Molekul dari Limbah Anorganik - Apipah, Siti Nurlelah; Farida, Ida; Sari, Sari (Jurnal Riset Pendidikan Kimia (JRPK), 2019)
This study aims to describe student activities, and analyze students' creative thinking abilities through project-based worksheets on the creation of molecular models of waste. The method used is a one-shot case study with the subjects of the sixth semester students of Chemistry Education Study Program Sunan Gunung Djati State Islamic University Bandung totaling 26 people. The results showed that student activity reached a very good category with an average percentage of 100%; the stages of identifying problems, making designs, carrying out research, and compiling drafts / prototypes reach very good categories with a percentage of 87%; the stage of measuring, assessing and improving products reaches an adequate category with a percentage of 83%. the finalization and publication stages of the product reached a good category with a percentage of 89%; The ability of students to think creatively in completing project-based worksheets reached an average score of 85 that is in level 4 included in the very creative category. Keywords Molecular models, waste, creative thinking, project-based worksheets.